The Role of North Sumatra NasDem Youth Guard (GPND Sumut) in the 2024 NasDem Party Political Contest in Medan City - Pasaribu, Defri Noval; Harahap, R Hamdani; Kusmanto, Heri (Riwayat: Educational Journal of History and Humanities, 2025)
The role of the North Sumatra NasDem Youth Guard (GPND) as a wing organization of the NasDem Party in the 2024 political contestation in Medan City were examined using qualitative descriptive research. This research aims to identify the role of the North Sumatra GPND in the political contestation of the NasDem Party, analyze the GPND's strategy in supporting candidates from the NasDem Party and determine the contribution of the North Sumatra NasDem Youth Guard in the political interests of the NasDem Party in 2024 in Medan City. The research results show that the North Sumatra GPND carries out three main roles: ideological, strategic and tactical which includes mobilization of young voters, political education, and political socialization of NasDem Party policies. The strategies used include door-to-door campaigns, use of social media, and collaboration with local communities. The contribution of the North Sumatra GPND not only helped win the candidate they were nominated, but also strengthened the NasDem party supporter base through cadre training and network building. This research provides insight into the importance of party wing organizations in supporting the sustainability of democracy and the success of elections in Indonesia